Analysis of the Influence of GDP, Health Index, Education Index, Consumer Price Index on Population in Central Java in 2010-2020 - Majreha, Vilo; Fatimah Nurhayati, Siti (JURNAL ILMIAH FEASIBLE: Bisnis, Kewirausahaan dan Koperasi, 2023)
This study aims to analyze the influence of Gross Regional Domestic Product (GRDP), Health Index, Education Index, and Consumer Price Index on the population of Central Java from 2010 to 2020. Time series panel data covering the specified period were analyzed using the fixed effects panel regression method. The study utilized secondary data from reliable sources. The analysis results reveal that GRDP has a significant positive influence on the population in Central Java, indicating that economic growth contributes to population increase. Moreover, the Health Index and Education Index also exhibit significant positive influences on the population, implying that well-being and educational quality foster population growth. However, the Consumer Price Index demonstrates a significant negative influence on the population. This suggests that high inflation rates might restrict population growth. In this context, it is crucial for governments and policy makers to consider the complex interactions among economic, social, and demographic factors while formulating sustainable development policies.